2015
DOI: 10.1080/13102818.2015.1038303
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofBacillus thuringiensissubsp.kurstakiHD1 spore-crystal mixture on the adults of egg parasitoidTrichogramma evanescens(Hymenoptera: Trichogrammatidae)

Abstract: In the present study, the potential hazard of Bacillus thuringiensis (Bt) kurstaki HD1 spore-crystal mixture (spore/ d-endotoxin) on parasitization performance and longevity of female egg parasitoid Trichogramma evanescens Westwood was evaluated. For this purpose, Bt kurstaki HD1 was incubated at 30 C in T3 medium at 200 rpm for seven days. Lyophilized spore-crystal mixture (5000 mg mL ¡1 ) was mixed with 50% honey solution and supplied to 0À24 h old T. evanescens adults as a nutrient to ensure the ingestion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The SEM images showed bipyramidal and cuboidal crystal morphologies of B. thuringiensis 225-15, 349-4, 417-1, 831-2, and 834-1 that were similar to most of the B. thuringiensis samples in Argentina, of which 88.8% of isolates containing cry1 and cry2 genes exhibited bipyramidal and cuboidal crystals (Sauka and Benintende 2017). The inclusion morphologies of B. thuringiensis serovar kurstaki HD1 have been reported to be bipyramidal and cuboidal structures (Monnerat et al 2007;Patel et al 2012;Zorzetti et al 2017); however, some publications reported that this strain contained bipyramidal, cuboidal, and spherical structures (Azizoglu et al 2015;Yılmaz et al 2012). Molecular mass analysis using SDS-PAGE showed the major bands of five effective isolate at approximately 130 and 65 kDa proteins, which were consistent with the 130 and 65 kDa proteins of the bipyramidal crystals of Cry1 proteins and the cuboidal crystals of Cry2 proteins, respectively (Azizoglu et al 2015;Patel et al 2012;Zorzetti et al 2017).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The SEM images showed bipyramidal and cuboidal crystal morphologies of B. thuringiensis 225-15, 349-4, 417-1, 831-2, and 834-1 that were similar to most of the B. thuringiensis samples in Argentina, of which 88.8% of isolates containing cry1 and cry2 genes exhibited bipyramidal and cuboidal crystals (Sauka and Benintende 2017). The inclusion morphologies of B. thuringiensis serovar kurstaki HD1 have been reported to be bipyramidal and cuboidal structures (Monnerat et al 2007;Patel et al 2012;Zorzetti et al 2017); however, some publications reported that this strain contained bipyramidal, cuboidal, and spherical structures (Azizoglu et al 2015;Yılmaz et al 2012). Molecular mass analysis using SDS-PAGE showed the major bands of five effective isolate at approximately 130 and 65 kDa proteins, which were consistent with the 130 and 65 kDa proteins of the bipyramidal crystals of Cry1 proteins and the cuboidal crystals of Cry2 proteins, respectively (Azizoglu et al 2015;Patel et al 2012;Zorzetti et al 2017).…”
Section: Discussionmentioning
confidence: 80%
“…The inclusion morphologies of B. thuringiensis serovar kurstaki HD1 have been reported to be bipyramidal and cuboidal structures (Monnerat et al 2007;Patel et al 2012;Zorzetti et al 2017); however, some publications reported that this strain contained bipyramidal, cuboidal, and spherical structures (Azizoglu et al 2015;Yılmaz et al 2012). Molecular mass analysis using SDS-PAGE showed the major bands of five effective isolate at approximately 130 and 65 kDa proteins, which were consistent with the 130 and 65 kDa proteins of the bipyramidal crystals of Cry1 proteins and the cuboidal crystals of Cry2 proteins, respectively (Azizoglu et al 2015;Patel et al 2012;Zorzetti et al 2017). Even Cry2 toxins which form cuboidal inclusion have been reported to exhibit dual toxicity against both lepidopteran and dipteran insects (Ribeiro et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The toxins produced by Bt israeliensis (Bti) are very specific and effective against dipteran pest, including mosquito and black fly, and thus has great demand in public health programmes (kills 95-100% of mosquito larvae within 24 h) (Land and Miljand 2014). Most of the Bt kurstaki (Btk) strains are active against lepidopteran pests, while strains of Bt tenebrionis (Btt) are active against coleopteran pests (Azizoglu et al 2015). The commercial Bt strains, their target pest, and their use in different sectors (agriculture, forestry, and public health programmes) are presented in Table 1.…”
Section: Insecticidal Bt Strains and Bt Toxinsmentioning
confidence: 99%